Calculated characters of leaves are independent on environmental conditions in Salix herbacea (Salicaceae) and Betula nana (Betulaceae) - Katarzyna Marcysiak (Acta Societatis Botanicorum Poloniae, 2012)
The goal of the study was to check if the shape-describing characters, calculated as ratios of the morphological measured traits are more stable, compared to the latter, and can be treated as independent on environmental conditions. The test was based on the example of leaves of Salix herbacea and Betula nana. The individuals of the two populations of S. herbacea from Tatra Mts. were divided into two groups: with bigger and smaller leaves. The two populations of B. nana came from different substrata: the first one, collected from the mire on the lower altitude, had bigger leaves, and the second, collected from the granite plateau and higher altitude, had smaller leaves.